Ultra-massive fluid transfusion in adult liver transplant recipients: A single center observational study - Hugh Slifirski; Nattaya Raykateeraroj; Angelica Armellini; Riley Hazard; Jordan Zalcman; Junyan Zhao; Zac Tran; Peter Le; Wendell Zhang; Michael Fink; Marcos Vinicius Perini; Anoop N. Koshy; et al. (PLoS ONE, 2025)
Introduction Patients undergoing liver transplantation may require large volumes of fluid to maintain hemodynamic stability and treat coagulopathy. This study aimed to determine the prevalence of ultra-massive fluid transfusion and to examine its association with clinical outcomes. We defined an ultra-massive fluid transfusion a priori as a transfusion volume of >20 liters of crystalloids, colloids, blood and blood products administered intraoperatively and within the first 24 hours postoperatively. Methods This single-center retrospective observational study included all adult patients who underwent an orthotopic liver transplant and received an ultra-massive fluid transfusion. The primary aim was to determine the prevalence of ultra-massive fluid transfusion in patients undergoing liver transplantation. Secondary objectives included evaluating the effect of the total volume of fluid and packed red blood cell transfusions on postoperative complications, mechanical ventilation hours, intensive care unit and hospital length of stay, and mortality. Results Of the 844 liver transplantation procedures, 81 (9.6%) required an ultra-massive fluid transfusion with a median transfusion volume of 36.8 liters (IQR: 31.2–48.7). Each additional liter of fluid administered during surgery was associated with an additional stay of 0.47 days in intensive care (95%CI: 0.18–0.76, p = 0.003). Each additional unit of packed red blood cells administered during surgery was associated with an additional 12.8 hours of mechanical ventilation (95%CI: 3.12–22.43, p = 0.014) and 1.0 additional day in intensive care (95%CI: 0.27–1.79, p = 0.012). Neither ultra-massive fluid transfusion nor packed red blood cell transfusions were associated with increased complications. Conclusion Approximately one in ten liver transplantation patients required an ultra-massive fluid transfusion. While ultra-massive fluid transfusion was associated with prolonged recovery, it was not associated with an increased risk of complications or mortality.